Dance of Gods in Indra’s Heaven - Temples of India Project Team (Jio Institute, 2024)
In the frieze of the drumming and dancing gods are Indra, seated on his elephant Airavata; a warrior holding a sword and shield, and an Apsara. Stella Kramrisch, in her work Hindu Temples (vol-2, plate LXVIII, p. 402-403) describes the spirit of the image in the following manner: 'the movement sways and surges to either side of a standing god who holds a long lance and seems to have ushered in before Indra the warrior so that he becomes one of the dancers. Indra, enthroned in a posture of ease, the right hand raised in Abhaya-mudra, grants fearlessness; his left-hand holds the Vajra. Small shapes surround him, Matali, his mahout, and companion spirits, Marut-like.' The elephant's trunk and the warrior's legs are interlaced; the warrior's is the largest movement; across the depth of the relief, he steps forward into the line of the celestials. Their dance vibrates, to the stamping of the feet, a suave tremor free from tension.” This image resonates with verse 7 of the Harsha stone inscription of Vigraharaja which mentions that the lord Harsha (Shiva) is worshipped on the hill by the joyous divine host, Indra.